KONSEP PENDIDIKAN SYED MUHAMMAD NAUQIB AL-ATTAS - Mustajab Ilham Labib; Mohammad Zakki Azzani (PAI RAFAH, 2023)
Education has become a human need that allows us to develop better from time to time. Many figures are from various civilizations including Islam and the West. Syed Muhammad Nauqib Al-Attas is one of the contemporary Islamic figures who focuses more on education, especially Islamic education. In general, views regarding the goals of education are divided into 2 types, both of which are at different levels. The first view is with a societal orientation, namely that education is an effort to form a society that has good attitudes, good attitudes here are good for government in the form of democracy, kingdom, or oligarchy. This research attempts to find Al-Attas’ Islamic education. This article is library research. Through his books, it is found that Al-Attas’s concept pf education is ta’dib. Ta'dib is the process of instilling adab in humans (students). Through proper Islamic education, Al-Attas aims to produce a man of adab, who is able to benefit an individual, society, and the state. For seeking Allah’s pleasure, the curriculum created by Al-Attas is divided into two, namely science fardhu of 'ain and science of fardhu kifayah, through these two sciences a man is expected to fulfill their needs as living beings. Without neglecting the importance of the knowledge of Islam as his worldview in learning science, a man requires a teacher to guide him. Teachers whose equipped with the right knowledge and adab properly can most possibly be a good example to their students.